Excited-state intramolecular proton transfer (ESIPT) fluorescence from 3-amidophthalimides displaying RGBY emission in the solid state. Issue 4 (24th January 2018) - Okamoto, Hideki; Itani, Kazumasa; Yamaji, Minoru; Konishi, Hiroyuki; Ota, Hiromi
Graphical abstract: Highlights: 3-Amido-substituted phthalimides display red-shifted fluorescence via ESIPT process. The ESIPT fluorescence features were qualitatively explained by (TD) DFT calculations. Amido-substituted phthalimides emit RGBY fluorescence in the solid state. Tf-amidophthalimides shows efficient ESIPT emission ΦF  = 0.50 in the solid state. Abstract: Fluorescence properties of phthalimide derivatives (1 ) incorporating sulfonamide and acetamide functionalities at the 3-position were investigated both in solution and in the solid states to reveal the effects of the amide functionalities on the fluorescence properties. In the solid state, sulfonamides1a and1b, respectively, gave off red (λ F max 595 nm) and green (λ F max 537 nm) emission through an ESIPT process. Acetamides1c and1d, respectively displayed blue (λ F max 432 nm) and yellow (λ F max 560 nm) emission. Through simply modifying the amide functionality, phthalimide1 displayed multicolor RGBY emission in the solid state.